Asymptotic finite fracture mechanics solution for crack onset at elliptical holes in composite plates of finite-width. (September 2017) - Felger, J.; Stein, N.; Becker, W.
Highlights: Asymptotic finite fracture mechanics analysis of crack onset at elliptical holes. Explicit relation of the incremental energy release rate. Comprehensive study on the validity range of the asymptotic solutions. Padé approximation for an improved convergence of the asymptotic expansions. Very good agreement between predictions and experimental data. Abstract: The onset of cracks at elliptical holes in finite-width laminated plates under uniaxial tension loading is investigated using a finite fracture mechanics approach. A coupled stress and energy criterion is applied in order to determine the effective strength of the notched plate and the size of instantaneously initiating cracks. A semi-analytical approach based on complex potential theory in combination with a two-scale asymptotic analysis is proposed leading to explicit relations for the stress field and energy quantities due to crack formation. This allows for an efficient finite fracture mechanics solution and a significant reduction of the numerical effort compared to a full-numerical treatment. The effect of higher-order terms in the asymptotic procedure and a technique leading to an improved convergence of the expansions are discussed in detail. A thorough comparison with numerical data is performed in order to analyse the validity range of the asymptotic solution. Furthermore, the failure load predictions are compared to experimental data from literature.